CONCERT LIFE IN RIGA AT THE END OF THE 18th CENTURY (1782–1800): EVIDENCE OF THE THEATERZETTEL COLLECTION (Mūzikas akadēmijas raksti, 2024)
The second half of the 18th century was a time of cardinal changes in Riga's music life. In this period, the tradition of regular public concerts was established. As in many other localities of the German-speaking cultural space, the main organizer of the concerts was the City Theatre (Rigaer Stadttheater). The members of the Theatre’s orchestra contributed significantly to the concert life of Riga both as soloists and as chamber musicians. The concert programs and posters from that time are available in the collection Theaterzettel (stored in the University of Latvia Academic Library). The study of this collection will allow to answer the questions: which music (prevailing genres, composers, etc.) was most often performed at that time in Riga, did the musical taste of the Rigans reflect the all-European tendencies of that time.